One-pot production of thermostable PHB biodegradable polymer by co-producing bio-melanin pigment in engineered Escherichia coli - Park, Seo A.; Yang, Yung Hun; Choi, Kwon Young (Biomass Conversion and Biorefinery, 2022)
In this study, to engineer a polyhydroxybutyrate (PHB) biopolymer, pyomelanin pigment was coproduced in a single Escherichia coli host and incorporated into PHB. The cells convert l-tyrosine into pyomelanin via the formation of homogentisate by expressing hydroxyphenylpyruvate dioxygenase (hppd), while producing PHB by expressing bktB, phaB, and phaC simultaneously. Up to 0.52 ± 0.16 g/L of sum of pyomelanin and PHB is produced, and its mixture (5.7% w/w) was emulsified in DMSO solution for pyoPHB film formation after sonication-induced nucleation of pyomelanin. To characterize the newly generated pyoPHB film, its color diagram, radical scavenging capacity, thermostability, and volume resistance are determined. The melting temperature and decomposition enthalpy increased in pyoPHB by 12%, and the antioxidant activity of the pyoPHB film increased by 16% compared to those of the control PHB film. Although the volume resistivity increased by more than 10 times, it is still within that of commercial plastics. Interestingly, more than 200 mg/L of pyomelanin could be stably produced in the co-producing host even though the PHB content was up to 50% level of cell mass and expression level of hppd was decreased by co-expression of PHB synthetic genes, which was estimated to be attributed to increased ATP pools. Therefore, finally, the ATP concentration in each of the pyomelanin- and PHB-producing cells was determined, resulting in a significant increase (up to fivefold) in the co-producing strain.
Keywords: Bio pigment; Co-production; Dioxygenases; Engineered escherichia coli; Engineered polyhydroxybutyrate; Melanin pigments; One pot; Polyhydroxybutyrate; Pyomelanin; Bio pigments; Co-production; Engineered PHB; PHB; Pyomelanin; Thermostability